The impact of global falsified medicines regulation on healthcare stakeholders in the legitimate pharmaceutical supply chain: a systematic review - Melia, Ellen; English, Aislinn; Naughton, Bernard D. (Frontiers in Medicine, 2024)
Background: Falsified medicine and their international regulation is an issue that impacts all healthcare sectors and their actors.These regulations aim to strengthen and protect the global pharmaceutical supply chain against falsified medicines. However, an evaluation of the impacts of these regulations on key stakeholders within the legitimate supply chain has not been explored.Objective: This research aimed to evaluate both the positive and negative impacts of falsified medicines regulation on key stakeholders within the global pharmacy sector including the manufacturer, wholesaler, hospital pharmacy, community pharmacy and the patient.Design: This research consists of a systematic review and thematic analysis concerning falsified medicines regulation and the subsequent impacts of existing global regulations on healthcare. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and checklist were utilized for reporting in this systematic review.A search of three databases, Embase, ProQuest and PubMed, was undertaken to determine studies applicable to the research question. The Mixed Methods Appraisal Tool (MMAT) was used to assess methodological quality and risk of bias for all included studies.From the initial 657 studies, a final set of 13 relevant studies were identified. The most frequently reported falsified medicines regulation was the Falsified Medicines Directive (FMD) [n=11]. The impact of falsified medicines regulation in the literature related to four areas: (1) Financial, (2) Social, (3) Organizational and (4) Pharmacy Practice Impacts. These common themes across the included studies frequently relate to challenges and/or concerns associated with falsified medicines regulation implementation as well as both the logistics and practicality of incorporating falsified medicines regulations into the daily operations.Implementation and enforcement of falsified medicines regulation does not yet appear to categorically fulfil the primary aim of the regulations, to strengthen the drug supply chain. However, in recent years, such regulations have challenged legitimate the pharmaceutical supply chain actors as they attempt to successfully implement these regulations. Studies mainly detail the negative impacts of regulation during the implementation phase but with the overall benefit pertaining to the prioritization and enhancement of patient care and safety within the healthcare sector.